Understand the Cultural Influence of Short Videos in the Communication of Public Health Information - Changning, Ren; Ghazali, Akmar Hayati Ahmad; Kamarudin, Syafila (Universitas Semarang, 2024)
Introduction: Groups with different ideologies have different perspectives on civilization and, therefore, can exhibit various cultural values. In today's globalized world, people from different cultural backgrounds interact through the web, and using emerging communication technologies, such as short videos, is a challenge, especially in public health. Although studies have shown that globalization can alter the process of cultural production and consumption and strengthen cultural identity, there are still differences in cultural production and cultural identity in public health. Methods: This study explored the differences in information understanding from different cultural contexts in the healthy cultural space and used qualitative analysis to explore these differences. Use of online ethnography for short video text objective observation and analysis. This study will take TIKTOK as the research object and analyze the feedback of different cultural groups on the problem in the real-time interaction of the subjects public health environment. Findings: This study reveals key differences in cultural communication strategies and highlights the challenges of cultural acceptance in both contexts. The findings provide fresh insights into how multiculturalism shapes and is influenced by the use of new media technologies in public health communication. Originality: This study provides novel insights into the unique communication practices of two specific social media accounts (@publichealthmsia and @健康中国). By focusing on their distinct challenges and approaches, it introduces innovative frameworks and guiding questions for addressing technical dilemmas in social media communication.